IMPOLITENESS STRATEGIES AND POWER PERFORMED BY NETIZENS ON TWITTER - Rugun Mastiar Pangaribuan; Rahmadsyah Rangkuti; Roma Ayuni Lubis (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2021)
This study aimed to find out the impoliteness strategy used by netizens in commenting on actor's tweets and the forms of tweet comments made by netizens. This study employs a descriptive qualitative method. The sources of data were tweeted by Jefri Nichol, one of the famous actors in Indonesia. In analyzing the data, the Theory of Culpeper (1996) describes the kinds of impoliteness strategies that netizens used in their tweet comments. This research shows that there are five data of tweet comments categorized into four types: bald on record impoliteness, positive impoliteness, negative impoliteness, and sarcasm or mock politeness. This research uses the Theory of Beebe (1995) and Bousfield (2008) for power performed, which categorized as superior, get authority over actions, dominate a conversation, emphasize the power hierarchy, and reactivate the power. The findings show that the netizens were angry and uncomfortable with Jefri's tweet because his tweet was like carrying someone's physical or face, where the things like this were a sensitive topic.